Effectiveness of nutrition training in improving cadres’ knowledge and skills in Kupang City - Astuti Nur; Santa Luciana Diaz Vera da Costa; Maria Goreti Pantaleon; Maria Helena Dua Nita; Anak Agung Ayu Mirah Adi (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting is still a major nutritional problem in the East Nusa Tenggara Province. Efforts to reduce stunting cannot be separated from the role of Posyandu cadres (integrated health post-cadres). This study aimed to determine the effects of anthropometric measurement training, toddler growth monitoring, and Infant and Young Child Feeding (IYCF) training on cadres' knowledge and skills. The research was a quasi-experiment with a pre-post-test control group design. The participants were Oesapa Health Center cadres who underwent purposive sampling in May-July 2024. Thirty intervention group cadres were given modules and training on monitoring growth, development, and IYCF for three days. Thirty cadres in the control group were provided with nutrition education and modules only. The cadres were then practiced at Posyandu. Data were collected through questionnaires and checklists. Data were analyzed using the Mann–Whitney U test. Results: There was an increase in cadre knowledge for all variables in both the intervention and control groups (p<0,05). The highest CGM was 21,33 points in the intervention group. CGM training also significantly improved cadre skills after Post-test 1 in the intervention group by 9,33 points (p= 0,000); however, at Post-test 2, there was no significant improvement (p= 0,934). In conclusion, nutrition training significantly improved cadres' knowledge scores and skills in conducting anthropometric measurements.